Fire Disaster Mitigation in Dense Settlements in Batu Merah Country - Hertine Megiestri Kesaulya; Resky Prafitri (International Journal of Science and Society, 2023)
Fire is a disaster that cannot be predicted when and where it will occur. Many fire disasters occur in dense settlements, so dense settlements become vulnerable to the danger of fire disasters. Negeri Batu Merah is one of the densely populated settlements located near the central area of Ambon City. This dense residential condition has resulted in settlements in Batu Merah Country becoming areas that are potentially vulnerable to fire disasters. This research aims to determine the distribution of fire disaster vulnerability levels in dense settlements in Batu Merah State. Apart from that, this research also aims to provide recommendations for reducing the level of fire vulnerability in the study area. The analytical methods used in this research are spatial analysis, appreciation analysis and descriptive analysis. Based on the results of the vulnerability analysis in the study area, the level of fire vulnerability is divided into three, namely low, high and very high levels of vulnerability. Interventions to reduce the level of fire vulnerability can be carried out by mitigating efforts both structurally and non-structurally by adding fire extinguishing facilities, widening residential roads, and widening roads in the Batu Merah settlements.